2022
DOI: 10.3389/fmed.2022.808318
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Trends in HIV/AIDS Burden Among Worldwide Regions From 1990 to 2019: A Secondary Analysis of the Global Burden of Disease Study 2019

Abstract: PurposeHIV/AIDS is a critical public health concern worldwide. This article investigated the spatial and temporal trends in HIV/AIDS burden from 1990 to 2019.MethodsData were extracted from the Global Burden of Disease (GBD) Study 2019. The estimated annual percentage change (EAPC) and the age-standardized rate (ASR) were used to quantify the change in trends at the global, regional, and national levels.ResultsIn terms of temporal trends, during the period 1990–2004, increasing trends in prevalence (EAPC = 7.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 57 publications
2
7
0
Order By: Relevance
“…Our study con rmed a decrease in the age-standardized DALY rates of HIV/AIDS in most countries or territories worldwide (a remarkable achievement) with global trends indicating considerable progress in curbing the HIV/AIDS pandemic over the past two decades. This trend was consistent with the sustained declines in HIV/AIDS incidence and mortality globally since 2005 [7,8,11], and with health system reforms undertaken to enhance access to and coverage of health care [25]. The reduced global burden of HIV/AIDS was attributed to a combination of efforts, including more effective prevention and control strategies as well as better treatment interventions, such as poverty alleviation, improvement of healthcare access, intensi ed international collaborations, health education, and other proximal ongoing contributions [5].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Our study con rmed a decrease in the age-standardized DALY rates of HIV/AIDS in most countries or territories worldwide (a remarkable achievement) with global trends indicating considerable progress in curbing the HIV/AIDS pandemic over the past two decades. This trend was consistent with the sustained declines in HIV/AIDS incidence and mortality globally since 2005 [7,8,11], and with health system reforms undertaken to enhance access to and coverage of health care [25]. The reduced global burden of HIV/AIDS was attributed to a combination of efforts, including more effective prevention and control strategies as well as better treatment interventions, such as poverty alleviation, improvement of healthcare access, intensi ed international collaborations, health education, and other proximal ongoing contributions [5].…”
Section: Discussionsupporting
confidence: 83%
“…We discovered that countries with a low GNI per capita were sharing an overwhelming burden of HIV/AIDS, though the global inequality has reduced over time. In previous studies, the total burden of HIV/AIDS, including both incidence and mortality, was heavier in most low and middle-income countries than in high-income ones [7,8,11]. It is widely acknowledged that income is a core social determinant in human health [42], and its distributional inequalities and imbalances may exert a substantially adverse impact on health nancing, access to healthcare, health insurance coverage, access to education, and health outcomes [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study from GBD 2017 provided a comprehensive assessment of global, temporal, and national trends in HIV incidence, prevalence, and mortality, but failed to deliver a detailed analysis of changes in the overall burden of HIV/AIDS [ 8 ]. Another recent study showed a declining trend in the global burden of HIV/AIDS over the past 15 years, with an unfavorable trend in high and middle-income countries [ 11 ]. In addition, previous studies have revealed widespread inequalities in HIV infection, testing, care, and awareness by gender, race, and income, especially in impoverished areas [ 12 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…More than 36 million individuals are living with human immunodeficiency virus (HIV), with approximately 1.7 million individuals acquiring the disease annually [ 1 , 2 ]. The global prevalence of HIV has continued to decrease over the last decade as a result of safer sexual practices and effective antiretroviral therapies (ARTs) that have proven to lower viral loads to undetectable levels and reduce the risk of transmission.…”
Section: Introductionmentioning
confidence: 99%